A Study of Physical, Chemical, and Sensory Characteristics of Novel Legume Dips - Lynda Makhloufi; Mohammad I. Yamani (International Journal of Food Science)
There is a consensus among experts and consumers that pulses are a good source of nutrients and fiber. In a traditional hummus recipe, chickpeas are the major ingredient. The present study is aimed at developing new legume dips by exchanging chickpeas (Chd) with dry green (Gld) and red lentils (Rld), dry white beans (Wbd), and dry green peas (Gpd). Presoaking, boiling, proximate composition, pH, energy, color measurement, and sensory evaluation were conducted on the dips using chickpea dip (hummus) as a control. One-way ANOVA was used to determine the differences between the dips. The results revealed significant differences in the proximate composition of legume dips. The protein content of the five samples ranged between 7.46% and 9.19%, while the values varied from 8.59% to 10.93% in fat, 3.88% to 6.54% in crude fiber, 14.48% to 15.51% in carbohydrates, 171.95 to 195.13 in energy, 1.55% to 1.76% in ash, and 63.35% to 66.90% in moisture. These variations could be attributed to the type and composition of each legume, the soaking and boiling process, and the tahini added during the preparation. pH ranged between 4.5 and 4.7. The color measurement indicated that the five legume dips could be considered bright products (high L∗>67), with a positive color valuebluered-green and yellow-. Significant differences (p≤0.05) were observed in the legume dips sensory evaluation, and the red lentil dip was the most acceptable with results comparable to the chickpea dip; it was followed by the green lentil, white bean, and green pea dips. These results highlight the feasibility of commercial production of legume dip that promotes human health and gives consumers more choices.